1993
DOI: 10.1152/ajpcell.1993.264.3.c603
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arginine vasopressin and atriopeptin on glial cell volume measured as 3-MG space

Abstract: This study evaluates the hypothesis that arginine vasopressin (AVP) and atriopeptin, peptide hormones synthesized and released within the brain, are regulators of brain cell volume using cultured astroglial cells derived from newborn rats. Cell water content, regarded as volume, was measured in defined, serum-free medium as the 3-O-methylglucose (3-MG) space. Initial experiments established conditions such that glucose, which competes with 3-MG for the glucose carrier, would not interfere with the measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…* P < 0.05 versus saline-treated controls with ischemic stroke [14]. It has previously been demonstrated that ICV administration of AVP significantly increases brain edema after cryogenic injury [50] and following cerebral ischemia [51]. The mechanisms of these set of observations are not fully elucidated at present.…”
Section: Role Of Avp In Brain Injury and In Evolution Of Cerebral Edemamentioning
confidence: 98%
“…* P < 0.05 versus saline-treated controls with ischemic stroke [14]. It has previously been demonstrated that ICV administration of AVP significantly increases brain edema after cryogenic injury [50] and following cerebral ischemia [51]. The mechanisms of these set of observations are not fully elucidated at present.…”
Section: Role Of Avp In Brain Injury and In Evolution Of Cerebral Edemamentioning
confidence: 98%
“…10 The hormone arginine vasopressin (AVP) was identified as a potential mediator of astrocytic cell swelling and subsequent fulminating edematous changes following cerebral injury. [11][12][13][14][15][16][17] It is thought that centrally-released AVP orchestrates the development of brain edema by inducing water and ionic movement. 18,19 Increased AVP levels activate the V1a receptor (V1aR), facilitate water transport across astrocytic cell membranes, and are associated with brain edema formation.…”
Section: Introductionmentioning
confidence: 99%
“…Although osmotic changes are part of a normal physiological response to maintain brain homeostasis, exaggerated swelling can lead to pathological conditions, for example triggering neuronal damage via the release of glutamate to the extracellular environment. Interestingly, NPs that are known to regulate water and electrolyte content in the brain have been reported to inhibit osmotic swelling in cultured astrocytes [65] and retina Müller cells [66]. Moreover, CNP and cGMP analogues have been shown to decrease intracellular pH in astrocytes by inhibiting a Na + /H + exchanger [67].…”
Section: Actions Of Cgmp In Astroglia and Microgliamentioning
confidence: 99%